Brewing complications: the effect of acute ethanol exposure on wound healing - Radek, Katherine A. (The Society for Leukocyte Biology, 2009)
Ethanol consumption is linked to a higher incidence of traumatic wounds and increases the risk for morbidity and mortality following surgical or traumatic injury. One of the most profound effects of acute ethanol exposure on wound healing occurs during the inflammatory response, and altered cytokine production is a primary component. Acute ethanol exposure also impairs the proliferative response during healing, causing delays in epithelial coverage, collagen synthesis, and blood vessel regrowth. The accumulated data support the paradigm that acute ethanol intoxication prior to injury significantly diminishes a patient’s ability to heal efficiently.